IMPROVING STUDENTS' READING ABILITY USING SHORT STORY AT GRADE VIII SMP NEGERI 1 TOMOHON - Gerson Tandi Kapang; Nihta Liando; Maikel Sanger (Program Studi Pendidikan Bahasa Inggris, 2022)
The short story is effective way in improving students’ reading ability at grade VIII SMP Negeri 1 Tomohon. This research aims to find out the effectiveness of short story in improving students’ reading ability at Grade VIII SMP Negeri 1 Tomohon. The research design employed in this research was true experimental. The population of this research was the students’ at grade VIII SMP Negeri 1 Tomohon and the sample was 20 students in the experimental group and 20 students in the control group. The result of data analysis showed that the experimental group got a mean score 84.25 than the control group got mean score 39.5. It means that, the mean score of the students in the experimental group was higher than for those in the control group. It showed that there is a significant improvement on students’ reading ability through short story and it indicated that short story is effective to improve students’ reading ability at grade VIII SMP Negeri 1 Tomohon. Regarding to the research findings, it is recommended to English teachers to use short story to improve the students’ reading ability. For the future researchers, it is also recommended to use the results of this research as a reference in employing similar research on the same or different language skills in different setting.